(untitled) (KYAMC Journal, 2017)
Purpose: We reviewed the literatures to see history, regimen of BCG and how BCG become a standard therapy for bladder carcinoma. Materials and Methods: We reviewed the previous literature describing the bacillus Calmette-Guerin (BCG) vaccine as an anticancer agent and its success as the most effective immunotherapy used against human bladder cancer and its adverse effects. Results: The association between tuberculosis and carcinoma is well established, It demonstrate that Bacillus Calmette-Guerin have immunological reactivity, inhibiting the tumor growth and progression in experimental animal models, led to clinical trials showing that intravesical Bacillus Calmette-Guerin eradicate and prevent recurrence and progression of superficial bladder carcinoma The exact mechanism of action of intravesical BCG instillation is still under investigation. However, it appears that BCG is mediated by the local immune response, mainly through T-helper cell response. It reduces the recurrence rate by an average of 40% and progression by more than 20% in papillary tumors, Carcinoma-in-situ over the patients without BCG therapy. Conclusions: For the last 45 yrs Bacillus Calmette- Guerin therapy has remained first line intravesical immunotherapy for superficial bladder cancer, an outstanding example of successful immunotherapy. KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 56-60